HUBUNGAN INDEKS MASSA TUBUH DAN FREKUENSI OLAHRAGA TERHADAP KEBUGARAN JASMANI PEKERJA KONSTRUKSI DI PT. PP (PERSERO) TBK TBK PROYEK APARTEMEN PINNACLE SEMARANG PINNACLE SEMARANG - Rio Rifki Nurfadli; Siswi Jayanti; Suroto Suroto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Type of works in PT. PP (Persero) Tbk Tbk were formwork, steel work and finishing. Almost all the types of works were physical work, hence requires optimal physical fitness. The factors could influence the physical fitness were nutritional status and physical activity frequence. The aim of this research was to knowing the relationship of nutritional status and physical activity frequence toward the physical fitness of the construction workers at PT. PP (Persero) Tbk Tbk Pinnacle Apartment Project of Semarang. This research used quantitative method with cross sectional approach. The population of this research were 84 workers with 45 respondents as the samples obtained using purposive sampling with quota sampling and data analyze used Kendall’s tau test. Most of respondents had normal category of nutritional status (77,8%), physical activity frequence seldom (77,8%), and below average physical fitness category (60.0%). Bivariate analysis of correlation body mass index toward physical fitness showed that (60.0%) workers with body mass index that belongs to normal had low physical fitness index, and bivariate analyze result of correlation physical activity frequence toward physical fitness showed that (70,0%) workers with high frequence of physical activity had moderate physical fitness index. The test result showed that there was no relationship between body mass index with physical fitness (p – value 0,878). There was relationship between physical activity frequence with physical fitness (p – value 0,004). Safety officer of the project should give safety sharing regarding the physical fitness to the workers, so that the workers will concern about their health.